Relation between metabolic performance capacity and test results on isokinetic movements by fin swimmers - Olbrecht, J.; Ungerechts, B.; Robben, B.; Mader, A.; Hollmann, W (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
In fin swimming the leg muscles are dominant during propulsion. It was felt that tests using isokinetic movements (Cybex) might provide some insight into the physical ability of the athletes' muscles. The purpose of this study was to compare performance and blood lactate response (BLa) to exercises in water with isokinetic measures. Fin swimmers (six male and eight female) of the German national team had their BLa and anaerobic thresholds (AT) assessed for 100 m and 400 m (V-4mM100 and V-4mM 400 ) swims using the 2 x 100 and 2 x 400 m twospeed tests (BLa100 max = BLa after lOO m sprint). Five maximal isokinetic extensions, peak torque (PKT) and average power (AP) of the repetition with the highest total work (TW) as well as BLa (BLa 60 ), total work (TW 6 ) and decrease of work (a5W) for 60 maximal repetitions were measure& for each leg and the different speeds. Blood lactate increased significantly after each test. Peak torque, AP, TW and TW 60 correlated with the 100 m sprint time, V-4mM 00 and BLa 100 max but not with V-4mM, 0 Q. Despite a strong relation between asw and both BLa100 max and BLaoO, BLa60 did not correlate with BLa 00 max. An increase of both V-4mM 400 and BLa 100 max improved PKT (multiple r = 0.87) but caused a greater asw. It can be concluded that PKT, AP, TV and TV 60 reflect the sprint performance capacity of fin swimmers. The Cybex results are related to the swim speclfic aerobic and anaerobic performance capacities. After the prolonged maximal test on land BLa was not related to BLa 1 0 max in water.